Examining the Relationship between Educated Entrepreneurs and Socio-Economic Factors: A Focus on Bangladesh Agricultural Inclinations - Apu, Mahedi Hasan; Kafayet, Kafayet Ullah; Sohan, Kazi Arifuzaman Sohan; Hossian, Md. Farhad Hossain; Amin, Dr. Md. Ruhul; Zafor, Hasan Abu (Jurnal Inovasi Bisnis dan Kewirausahaan, 2024)
This paper explored the perception of farming as a career among educated jobseekers in Bangladesh. We analyze how socio-economic determinants influence their perceptions and investigate the obstacles that prevent or limit their potential engagement in the farming sector. The analysis is conducted with a sample size of 509 and suitable analysis procedure such as descriptive statistics, SWOT analysis, overall weighted mean of career choice criteria, logistics regression, and partial least square discriminant analysis (PLS-DA) are applied. The result indicates that rural life, economic condition, and family influence play significant role in shaping educated job seekers in Bangladesh having interest in farming. It also suggests that there is a gap between the interest and the knowledge of farming among the respondents. The study also implies that rural residence, entrepreneurial intention, prior farming experience, and financial resources are key factors driving interest in farming career. In the following study the constructed PLS-DA model is highly accurate and reveals the factors that motivate people to pursue farming. Overall, this study suggests that developing and implementing vocational and technical training programs for young people that help them to move towards farming sector.